Identifying and Categorizing The Different Types of References Used in All The World’s A Stage By William Shakespeare - Ninda Prabawati; Masda Surti Simatupang (Prodi Sastra Inggris UKI, 2023)
Reference is an important aspect of the learning process, especially in analyzing discourse, both in the forms of scientific texts and literary works such as drama, prose, and poetry. Two concepts of reference are used: the kinds of referents and ways of referring. Kinds of referents include unique or non-unique, concrete or abstract, and countable or non-countable referents. Meanwhile, the ways of referring include a generic or non-generic, specific or non-specific, and definite or indefinite reference. These two concepts are used to identify and categorize referents in the poem “All the World’s a Stage” by William Shakespeare. Categorizing referents can help reveal some of the referents used by Shakespeare in the poem. Analyzing references in poetry can enrich understanding in analyzing literary works more deeply. Even so, the results of each researcher’s analysis may differ depending on how each individual interprets the poem.